2010 IEEE International Symposium on Information Theory 2010
DOI: 10.1109/isit.2010.5513492
|View full text |Cite
|
Sign up to set email alerts
|

Performance tradeoffs for exact support recovery of sparse signals

Abstract: Abstract-We study the tradeoffs between the number of measurements, the signal sparsity level, and the measurement noise level for exact support recovery of sparse signals via random noisy measurements. By drawing analogy between exact support recovery and communication over the Gaussian multiple access channel, and exploiting mathematical tools developed for the latter problem, we derive sharp asymptotic sufficient and necessary conditions for exact support recovery. Specifically, when the number of nonzero e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…We have established sufficient conditions on the measurement rate to ensure partial detection of the support set based on the relative power of the non-zero entries in the sparse signal. This builds on and extends the results in [7,8,9], which considered only perfect recovery of the support set.…”
Section: Related Prior Work and Conclusionsupporting
confidence: 57%
See 2 more Smart Citations
“…We have established sufficient conditions on the measurement rate to ensure partial detection of the support set based on the relative power of the non-zero entries in the sparse signal. This builds on and extends the results in [7,8,9], which considered only perfect recovery of the support set.…”
Section: Related Prior Work and Conclusionsupporting
confidence: 57%
“…The asymptotic tradeoffs for exact support set recovery in a noisy setting were studied in [7,8,9]. Further, asymptotically achievable Cramér-Rao bounds on the mean-square estimation error (MSE) were given in [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the noiseless environment (i.e., Z = 0), sufficient conditions to exactly recover the support of the sparse signal have been derived in [3]- [5]. In the presence of measurement noise, information theoretic tools have proven useful in understanding the performance tradeoff for support recovery of sparse signals [6]- [10]. In particular, Jin et al [10] identified the connection between the problem of sparse signal support recovery and the problem of communication over Gaussian multiple access channel (MAC), based on which they derived sharper asymptotic tradeoffs between the signal dimension, the number of nonzero entries, and the number of measurements for exact support recovery in the noisy setting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, so called, diversity effect is discussed through which the block-sparsity can further reduce the minimum number of measurements, especially in the regime of moderate and low SNR. Our work can be viewed as a generalization of the work in [10] in the sense that we interpret our problem as the problem of communications over Gaussian multi-input and single-output (MISO) MAC.…”
Section: Introductionmentioning
confidence: 99%